Roman virtue in the early Christian thought of Lactantius - Gehrke, Jason M. (Oxford Studies in historical theology series, 2025)
"Known since the Renaissance as the 'Christian Cicero,' Lucius Caecilius Firmianus Lactantius (d. 324 A.D.) was a professor of Latin rhetoric, Christian apologist, and theologian at Constantine's court. Writing in response to Diocletian's persecution, he attempted a complete synthesis of third-century Latin Christian thinking about theology, ethics, and political order. This work explores the character and quality of that synthesis in his major work, The Divine Institutes of the Christian Religion by focusing on the core notion of virtus. The early chapters explore the socio-political (Chapter 1) and philosophical traditions that informed arguments about virtus in classical Roman (Chapter 2) and early Latin Christian writers - especially Tertullian, Minucius Felix, and Cyprian (Chapter 3)"--